2021
DOI: 10.1021/acs.oprd.0c00520
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Process Development for the Final Step of the Biocatalytic Synthesis of Islatravir: Comprehensive Crystal Engineering for a Low-Dose Drug

Abstract: Islatravir (MK-8591), a highly potent nucleoside reverse transcriptase translocation inhibitor, is being developed to stem the spread of global HIV infections. Following a nine-enzyme in vitro synthesis of islatravir from 2-ethynylglycerol without intermediate isolation, a crude active pharmaceutical ingredient with high levels of biological and chemical impurities must be purified through recrystallization. With efficacy at sub-milligram doses, islatravir requires a robust crystallization method for consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…31 Wet milling before a thermal cycle can also lead to more effective purification due to exposure of the interior of crystals for ripening, as demonstrated in the SINTAX (shear induced nucleation and thermal annealing) process for islatravir. 51 As consistently shown in SLIP tests with impurities forming solid solutions (Figures 5 and 6), the highest impurity level is observed in the liquid phase when the material is in contact with the first drop of solvent. Therefore, a series of agitated cake washes may lead to dissolution of the dirtiest fraction of solids, leading to a desired improvement in overall purity.…”
Section: Process Development Strategies For Improved Purificationsupporting
confidence: 63%
See 1 more Smart Citation
“…31 Wet milling before a thermal cycle can also lead to more effective purification due to exposure of the interior of crystals for ripening, as demonstrated in the SINTAX (shear induced nucleation and thermal annealing) process for islatravir. 51 As consistently shown in SLIP tests with impurities forming solid solutions (Figures 5 and 6), the highest impurity level is observed in the liquid phase when the material is in contact with the first drop of solvent. Therefore, a series of agitated cake washes may lead to dissolution of the dirtiest fraction of solids, leading to a desired improvement in overall purity.…”
Section: Process Development Strategies For Improved Purificationsupporting
confidence: 63%
“…In this context, it has been demonstrated that impurity gradients within a crystal can undergo intra-particle ripening leading to the fast dissolution of impurity-rich cores . Wet milling before a thermal cycle can also lead to more effective purification due to exposure of the interior of crystals for ripening, as demonstrated in the SINTAX (shear induced nucleation and thermal annealing) process for islatravir …”
Section: Process Development Strategies For Improved Purificationmentioning
confidence: 99%
“…As the observed ripening phenomena are linked to the formation of solid solutions with impurities, it is expected that this ripening mechanism may not be exclusive to SA but in fact may be quite general for organic compounds, especially when crystallized in the presence of structurally similar impurities. Another example was recently reported that described variable impurity rejection and dirty crystal cores during the crystallization of the pharmaceutical compound Islatravir . In this case, the dirty crystal cores could be exposed to the surrounding solution and dissolved by breaking the crystals by wet milling and thermal annealing.…”
Section: Resultsmentioning
confidence: 85%
“…Another example was recently reported that described variable impurity rejection and dirty crystal cores during the crystallization of the pharmaceutical compound Islatravir. 25 In this case, the dirty crystal cores could be exposed to the surrounding solution and dissolved by breaking the crystals by wet milling and thermal annealing. However, the formation of specifically tubular crystals is directly dependent on the inherent crystal morphology.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…Navigating through each possible impurity incorporation mechanism could be a cumbersome exercise when working on a process with multiple steps, multiple impurities, limited material availability, and short timelineswhich is typically the case in pharmaceutical development. There are several case studies available that have control strategies targeted toward identifying singular impurity incorporation mechanisms. Recently, Urwin et al from the Continuous Manufacturing and Advanced Crystallization (CMAC) consortium, representing an academic and industrial collaboration, demonstrated a workflow that brings together the large body of literature to systematically diagnose the cause of impurity incorporation and design a control strategy to get optimal impurity rejection. The workflow reduces the experimental burden by logically prioritizing the experiments needed based on several checkpoints.…”
Section: Introductionmentioning
confidence: 99%